Surrogate Relaxations Approaches for a Capital Budgeting Model - Costa, A.; Paixão, J. P. (Congresso da APDIO - IO 2015, 2015)
We present and discuss surrogate constraint relaxations for a scenario based capital budgeting model that captures risk uncertainty and managerial flexibility, maximizing the time-varying of a portfolio of investment options. For this linear integer programming model, we derive and computationally test rules for initializing and updating the constraint weights relating to the surrogating process. To compare the different surrogate relaxation approaches, an extensive computational experience was carried out for a set of large scale test instances previously considered in the literature.